Pharmacokinetic Evaluation of Neutral Sphinghomyelinase2 (nSMase2) Inhibitor Prodrugs in Mice and Dogs - Arina Ranjit; Chae Bin Lee; Lukáš Tenora; Vijaya Saradhi Mettu; Arindom Pal; Jesse Alt; Barbara S. Slusher; Rana Rais (Pharmaceutics)
Background: Extracellular vesicles (EVs) can carry pathological cargo, contributing to disease progression. The enzyme neutral sphingomyelinase 2 (nSMase2) plays a critical role in EV biogenesis, making it a promising therapeutic target. Our lab previously identified a potent and selective inhibitor of nSMase2, named DPTIP (IC50 = 30 nM). Although promising, DPTIP exhibits poor pharmacokinetics (PKs) with a low oral bioavailability (%F < 5), and a short half-life (t1/2 ≤ 0.5 h). To address these limitations, we previously developed DPTIP prodrugs by masking its phenolic hydroxyl group, demonstrating improved plasma exposure in mice. Recognizing that species-specific metabolic differences can influence prodrug PK, we expanded our studies to evaluate selected prodrugs in both mice and dogs. Methods: The scaleup of selected prodrugs was completed and two additional valine- ester based prodrugs were synthesized. Mice were dosed prodrugs via peroral route (10 mg/kg equivalent). For dog studies DPTIP was dosed via intravenous (1 mg/kg) or peroral route (2 mg/kg) and prodrugs were given peroral at a dose 2 mg/kg DPTIP equivalent. Plasma samples were collected at predetermined points and analyzed using developed LC/MS-MS methods. Results: In mice, several of the tested prodrugs showed similar or improved plasma exposures compared to DPTIP. However, in dog studies, the double valine ester prodrug 9, showed significant improvement with an almost two-fold increase in DPTIP plasma exposure (AUC0–t = 1352 vs. 701 pmol·h/mL), enhancing oral bioavailability from 8.9% to 17.3%. Conclusions: These findings identify prodrug 9 as a promising candidate for further evaluation and underscore the critical role of species-specific differences in prodrug PKs.